Corporality, work and knowledge: an approach to understanding subjectivity in the context of the “country life” - Leila Martina Passerino (Revista Latinoamericana de Estudios sobre Cuerpos, Emociones y Sociedad)
The work takes the dimension of corporeality as significant for the study of certain types of constitution and transformation of subjectivities in the context of the “country life”. As part of a larger research project, the voice of owners and labourers currently living in rural areas who work with farming and cattle at Santa Fe and Entre Rios provinces, are pick up again. The study of corporeality as the backbone of the studies of culture and subjectivity is proposed. The dialogue between Merleau-Ponty and Pierre Bourdieu is in this field a fertile direction for analysing work processes and knowledge, considered as particular modality of production of subjectivity in the “country”, understood as a living style.